Handbook on Artificial Intelligence-Empowered Applied Software Engineering VOL.1: Novel Methodologies to Engineering Smart Software Systems - Virvou, Maria; Tsihrintzis, George A.; Bourbakis, Nikolaos G.; Jain, Lakhmi C. (Artificial Intelligence-Enhanced Software and Systems Engineering, 2022)
XII, 329 p. 242 illus., 102 illus. in color.